Analysis Of Leverage, Liquidity, And Profitability On Dividend Policy (A Study Of Companies In The Food And Beverage Sub-Sector Listed On The Indonesia Stock Exchange In 2018-2022) - Aminah, Wiwin; Nazah, Mohammad Angga Saefun (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Dividend policy is a policy regarding the distribution of dividends to shareholders decided by the company within a specific period. The amount of dividends distributed depends on the joint decision along with various considerations. This research analyze the influence of leverage, liquidity, and profitability on dividend policy. The sampling technique used is purposive sampling, resulting in 14 companies with a span\of of 5 years, making a total of 70 samples in this research. This research employ’s a quantitive method, and it is a descriptive study. The analysis method employed in this study is panel data regression. The results obtained through descriptive statistics and panel data testing with the common effect model, indicate that leverage, liquidity, and profitability variables collectively have impact on dividend policy. Specifically, Leverage doesn’t have impact, liquidity has a positive influence, and profitability has a negative impact on dividend policy of the food and beverage subsector listed on the Indonesia Stock Exchange for years 2018 through 2022.